Biodegradation of combined pollutants of polyethylene terephthalate and phthalate esters by esterase-integrated Pseudomonas sp. JY-Q with surface-co-displayed PETase and MHETase - Haixia Wang; Jiahong Zhu; Meng Sun; Mengjie Gu; Xiya Xie; Tongtong Ying; Zeling Zhang; Weihong Zhong (Synthetic and Systems Biotechnology)
The waste pollution problem caused by polyethylene terephthalate (PET) plastics poses a huge threat to the environment and human health. As plasticizers, Phthalate esters (PAEs) are widely used in PET production and become combined pollutants with PET. Synthetic biology make it possible to construct engineered cells for microbial degradation of combined pollutants of PET and PAEs. PET hydroxylase (PETase) and monohydroxyethyl terephthalate hydroxylase (MHETase) isolated from Ideonella sakaiensis 201-F6 exhibit the capability to depolymerize PET. However, PET cannot enter cells, thus enzymatic degradation or cell surface displaying technology of PET hydrolase are the potential strategies. In this study, Pseudomonas sp. JY-Q was selected as a chassis strain, which exhibits robust stress tolerance. First, a truncated endogenous outer membrane protein cOmpA and its variant Signal (OprF)-cOmpA were selected as anchor motifs for exogenous protein to display on the cell surface. These anchor motifs were fused at the N-terminal of PET hydrolase and MHETase and transformed into Pseudomonas sp. JY-Q, the mutant strains successfully display the enzymes on cell surface, after verification by green fluorescent protein labeling and indirect immunofluorescence assay. The resultant strains also showed the catalytic activity of co-displaying PETase and MHETase for PET biodegradation. Then, the cell surface displaying PET degradation module was introduced to a JY-Q strain which genome was integrated with PAEs degrading enzymes and exhibited PAEs degradation ability. The resultant strain JY-Q-R1-R4-SFM-TPH have the ability of degradation PET and PAEs simultaneously. This study provided a promising strain resource for PET and PAEs pollution control.